Pathological aspects of disseminated protothecosis-like infection in a dog - Bindaco, Adriano Lima Stelzer; Silva, Halana Do Carmo; Ferraz, Carolina Magri; Tobias, Fernando Luiz; Flecher, Mayra Cunha; Senhorello, Igor Luiz Salardani [UNESP] (FapUNIFESP (SciELO), 2024)
Anatomopathological descriptions of infections caused by saprophytic algae in dogs are rare. This study reported the anatomopathological and microbiological findings suggestive of disseminated protothecosis in a dog residing in the state of Espírito Santo, Brazil. During necropsy, macroscopic alterations were observed in peripheral lymph nodes, heart, kidneys, pancreas, and lungs. Microbiological, cytological, and histopathological examinations were performed. Cytology and histopathology revealed piogranulomatous inflammation associated with sporangia and endospores, while microbiological culture suggested the growth of Prototheca spp.. These anatomopathological and microbiological findings were crucial for diagnosing and documenting the first case of disseminated Prototheca spp. compatible infection in a dog in the state of Espírito Santo, Brazil.
Aspectos patológicos de uma infecção disseminada semelhante à Prototecose em um cão
Keywords: canine; infection; lgae; Prototheca; systemic lesions